PERBEDAAN ASUPAN ZAT GIZI MIKRO, KEJADIAN GIZI LEBIH DAN TEKANAN DARAH PADA SANTRIWATI BOARDING SCHOOL YANG MEMILIKI AHLI GIZI DAN TANPA AHLI GIZI - Diaz Isfahami Fitri, (2023)
The role of nutritionist on food service in boarding school institutions is rarely applied by the boarding schools, however the role of nutritionist is crucial for students in order to meet their nutritional needs by supervising their nutritional values and intakes. The goal is to analyzed the differences between micronutrients intakes (natrium and iron), high incidence of nutrition and blood pressure amongst students in boarding schools with and without nutritionist. The research is using quantitative methods with cross sectional design. The samples are 79 respondents from each boarding schools which resulting in total 158 respondents and were chosen by stratified random sampling technique. The data were analyzed by Mann Whitney for numerical data and Chi Square for categorical data. Results: There are the differences between iron intakes amongst Al-Hamidiyah students and Dwiwarna Boarding School student (p-value = 0.000).